Notes and comments - Urbano, Henrique Osvaldo (1976)
1. How to define peasant religion?, 2. Gregorio or the logic of Andean thought, 3. ... the Collaguas, vertically speaking..., 4. Andean ideologies in Huancayo, 5. Runes in the National Institute of Culture.